Noncompact and slender concrete-filled steel tubes under axial compression: Finite-element modeling and evaluation of stress-strain models for fiber-based analysis. (September 2022) - Subedi, Naresh; Obara, Taku; Kono, Susumu
Abstract: This study provides guidelines for the detailed finite-element modeling and efficient fiber-based analysis of noncompact/slender CFSTs under axial compression. To this end, a finite-element model capable of explicitly simulating the interaction between the concrete and steel tube is developed in LS-DYNA. The accuracy of the proposed model is verified using a database of ninety-six noncompact and slender CFSTs compiled from the literature. In addition, seven sets of most commonly used stress-strain models for the fiber-based analysis of CFSTs are briefly reviewed. The suitability of the stress-strain models to simulate the behavior under axial compression is evaluated using the experimental data in the compiled database and the finite element analysis results. The results show that the proposed finite-element model reasonably simulates the axial compression response of noncompact and slender CFSTs. For the fiber-based approach, Sakino's model gives the best prediction of the full-range axial load-displacement response. Findings from this study will help the designers and researchers to select appropriate modeling approaches and model parameters for the design and analysis of noncompact and slender CFSTs. Highlights: Database of 96 noncompact and slender concrete-filled steel tube (CFST) column tests collected from the literature. A finite-element model is developed to accurately simulate the behavior of noncompact/slender CFSTs under axial compression. Accuracy of existing stress-strain models is evaluated for the fiber-based analysis. Recommendations for detailed finite-element modeling and efficient fiber-based analysis of noncompact and slender CFSTs.